Does trust in organization mediate the influence of servant leadership on satisfaction outcomes among flight attendants? - Ilkhanizadeh, Shiva; Karatepe, Osman M. (Emerald Group Publishing Ltd, 2018)
Purpose Drawing from servant leadership (SL) and social exchange theories, our study investigates trust in organization (TIO) as a mediator of the impact of SL on job, career and life satisfaction. Design/methodology/approach A time-lagged survey design was used to gather data from flight attendants in Turkey. Structural equation modeling was used as the main analytic tool to assess these relationships. Findings The relationships proposed in the authors' study receive full support from the empirical data. Specifically, TIO is one of the immediate outcomes of SL that engenders job, career and life satisfaction at elevated levels. The results highlight the impacts of job and career satisfaction in the intermediate linkage between SL and life satisfaction. Practical implications Management should train managerial employees to enhance the understanding of SL, which boosts flight attendants' TIO. Management should invest in human resources through training and empowerment. This makes flight attendants perceive that management does not violate psychological contract. Such employees develop TIO that in turn engenders higher job, career and life satisfaction. It is also important to reward servant leaders when they succeed in making flight attendants develop TIO and motivating them to have higher job performance. Originality/value Little is known about the consequences of SL in the extant service research. More importantly, there are still calls for research about the variables (e.g. TIO) mediating the relationship between SL and employee satisfaction outcomes.
Keywords: Servant leadership; Trust; Employee satisfaction